PAWON CATERING BUSINESS MARKETING STRATEGY IN KALITENGAH VILLAGE CIREBON - Marogi, Helmi; Saefullah, Eef; Wasman, Wasman (Politeknik Siber Cerdika Internasional, 2023)
The purposes of this research are: to (1) Acknowledege marketing strategy of the Pawon Catering business; (2) Knowing the marketing effectiveness of Pawon Catering business; (3) Knowing the obstacles faced by Pawon Catering in conducting marketing. This study uses a descriptive qualitative research method that focuses on the MSME sector with the type of halal food, namely the catering business, with data collection techniques namely observation, interviews, and documentation techniques to Mrs. Lis as the founder of the business and her employees. Data analysis techniques were carried out in four stages, namely: analysis, reduction, display, and concluding. The results of this study indicate that the Pawon Catering business is running effectively, this is focused on the marketing strategy carried out where the marketing strategy has developed and increased because it utilizes technological aspects and the use of social media to attract the interest of potential consumers so that people become interested in using these products. Therefore, in terms of business, Pawon Catering is an effective business and has benefits for the surrounding community. This research is expected to be useful for the community and business actors in adding insight into the economy.